Serum apolipoprotein B increased among tuberculosis patients compared to healthy subjects - Ihim, Augustine Chinedu; Meludu, Samuel Chukwuemeka; Onyenekwe, Charles Chinedum; Anyabolu, Arthur Ebelenna; Akujiobi, Comfort N (Faculty of Medicine, Universitas Trisakti, 2021)
BackgroundThe burden of tuberculosis (TB) and cardiovascular disease (CVD) is enormous worldwide. Public health programs have been challenged with the overlapping of TB and CVD epidemics.Mycobacterium tuberculosisÂ (MTB) is also a main driver of atherogenesis, suggesting a potential pathogenic role of tuberculosis in cardiovascular disease. The objective of this study was to compare the serum levels of apolipoprotein B (apo B), apolipoprotein B48 (apo B48) and apolipoprotein B100 (apo B100) between patients with tuberculosis and healthy subjects. Methods A cross-sectional study was conducted involving 251 subjects consisting of 120 treatment naÃ¯ve active TB patients [26 HIV co infected (TB+HIV+) and 82 TB+), 12 malaria parasite co-infected (TB+MP+)], 26 latent TB infected (LTB) and 105 healthy controls. Their body mass index (BMI) was calculated. Mycobacterium tuberculosis infection was determined by Ziehl-Nelseen (ZN) sputum smear microscopy and confirmed positive using GeneXpert. Latent TB was determined by Mantoux test, MP was evaluated by microscopy while HIV by immunochromatographic techniques using serial algorithm. Apolipoproteins were determined using spectrophotometry. A one-way ANOVA test and LSDâ€™s post hoc multiple comparisons were used for statistical analyses. ResultsSignificantly lower mean levels of BMI were observed in LTB, TB+, TB+HIV+ and TB+MP+ compared with the controls (p<0.005). The mean serum levels of apo B, apo B48 and B100 were significantly higher in LTB, TB+, HIV+TB+ and TB+MP+ compared with apparently healthy controls (p<0.05). Conclusion Elevated levels of apolipoproteins among infected TB individuals might predispose them to cardiovascular disease.